Tool management in manufacturing systems equipped with CNC machines - Giovanni Tani (Production)
This work has been carried out for the purpose of realizing an automated system for the integrated management of tools within a company. By integrating planning, inspection and tool-room functions, automated tool management can ensure optimum utilization of tools on the selected machines, guaranteeing their effective availability. The first stage of the work consisted of defining and developing a Tool Management System whose central nucleus is a unified Data Base for all of the tools, forming part of the company's Technological Files (files on machines, materials, equipment, methods, etc.), interfaceable with all of the company departments that require information on tools. The system assigns code numbers to the individual components of the tools and file them on the basis of their morphological and functional characteristics. The system is also designed to effect assemblies of tools, from which are obtained the "Tool Cards" required for compiling working cycles (CAPP), for CAM programming and for the Tool-room where the tools are physically prepared. Methods for interfacing with suitable systems for the aforesaid functions have also been devised